Kurikulum PGRA Berbasis Kecerdasan Spiritual - Kisbiyanto, Kisbiyanto (THUFULA, 2016)
Childhood education is specific education because of its early education.C Childhood education is also a beginning to form Islamic personality. This specificeducation needs teachers who have competences, especially spiritual quotion.This study is a research with qualitative approach, focused on how the curriculumof PGRA. The main data collecting is study of documents, with description andanalysis. The result of this study is the curriculum of PGRA in STAIN Kudus consistsof spiritual quotion education for teacher training.